Effects of education to facilitate knowledge about chronic pain for adults: a systematic review with meta-analysis. Issue 1 (December 2015) - Geneen, Louise; Martin, Denis; Adams, Nicola; Clarke, Clare; Dunbar, Martin; Jones, Derek; McNamee, Paul; Schofield, Pat; Smith, Blair
Abstract Background Chronic pain can contribute to disability, depression, anxiety, sleep disturbances, poor quality of life and increased health care costs, with close to 20 % of the adult population in Europe reporting chronic pain. To empower the person to self-manage, it is advocated that education and training about the nature of pain and its effects and how to live with pain is provided. The objective of this review is to determine the level of evidence for education to facilitate knowledge about chronic pain, delivered as a stand-alone intervention for adults, to reduce pain and disability. Methods We identified randomised controlled trials of educational intervention for chronic pain by searching CENTRAL, MEDLINE, EMBASE and ongoing trials registries (inception to December 2013). Main inclusion criteria were (1) pain >3 months; (2) study design that allowed isolation of effects of education and (3) measures of pain or disability. Two reviewers independently screened and appraised each study. Results Nine studies were analysed. Pooled data from five studies, where the comparator group was usual care, showed no improvement in pain or disability. In the other four studies, comparing different types of education, there was no evidence for an improvement in pain; although, there was evidence (from one study) of a decrease in disability with a particular form of education—pain neurophysiology education (PNE). Post-hoc analysis of psychosocial outcomes reported in the studies showed evidence of a reduction in catastrophising and an increase of knowledge about pain following PNE. Conclusions The evidence base is limited by the small numbers of studies, their relatively small sample sizes, and the diversity in types of education studied. From that limited evidence, the only support for this type of education is for PNE, though it is insufficiently strong to recommend conclusively that PNE should be delivered as a stand-alone intervention. It therefore remains sensible to recommend that education be deliveredin conjunction with other pain management approaches as we cannot confidently conclude that education alone is effective in reducing pain intensity or related disability in chronic pain in adults.